Collaborate or perish: water resources management under contentious water use in a semiarid basin. Issue 4 (1st October 2020) - Galvez, Victor; Rojas, Rodrigo; Bennison, Gabriella; Prats, Camilo; Claro, Edmundo
ABSTRACT: Collaboration among stakeholders is an underpinning concept behind water resources management. It sustains planning/visioning processes by sharing and transferring knowledge/resources, promoting stakeholder engagement, building trust and resolving conflict. In recent years, a shift towards collaboration-based approaches to water management and governance has been observed. Despite clear advantages such as reducing transaction costs of collaboration, improved responsiveness to solve complex issues and ample deliberative capacity, a clear gap between theory and practice has been identified. In this work, we argue that conditions other than the collaborative process itself may facilitate or hinder collaboration among stakeholders. Our analysis is therefore focused on the starting conditions, institutional design and facilitative leadership aspects of the collaborative governance framework. Using semi-structured interviews with key stakeholders and thematic coding analysis we identify barriers and enablers for successful collaboration in the contentious semiarid Copiapó River Basin (Chile). Results indicate that major barriers correspond to lack of a shared vision, lack of effective leadership and political will, and specific knowledge, power and resource asymmetries. Enablers identified include interdependency among stakeholders, awareness of water issues and previous conditions of collaboration. Despite stakeholders recognizing an impending need to collaborate, starting conditions supporting collaborative efforts are rather weak in the Copiapó River Basin.